Economic governance in Europe : comparative paradoxes, constitutional challenges - Fabbrini, Federico, 1985- (Oxford : Oxford University Press, 2016)
Offering an comparative examination of the constitutional implications of the Euro-crisis on vertical and horizontal relations of power in the EU, this book proposes new ways in which to perfect the governance of Economic and Monetary Union.
Specialized.
Description based on online resource; title from home page (viewed on March 9, 2016).
Keywords: European Union; European Union countries -- Economic policy; Law; International law